Пристрій для завантаження сипких матеріалів в клапанні мішки - Оришака, О. В.; Кравцов, А. О.; Оришака, В. О.; Артюхов, А. М.; Oryshaka, O.; Kravtsov, A.; Oryshaka, V.; Artiukhov, A.; Оришака, О. В.; Кравцов, А. А.; Оришака, В. А.; Артюхов, А. Н. (Український інститут промислової власності, 2008)
Корисна модель відноситься до фасувально-пакувального обладнання і може бути використаний в агропромисловості, будівельній, хімічній та інших галузях господарства, а також на підприємствах, які здійснюють фасування сипких матеріалів. A device for loading of bulk materials into the valve bags, which contains a bunker with outlet funnel, valve, which is located at the outlet from the bunker, product pipe installed with possibility to achieve oscillating motions relative to its hinge mount to the outlet funnel of the bunker, loading and weight gage devices, systems of compressed air and automation.
Device for loading of bulk materials into the valve bags